1978
DOI: 10.1099/00221287-106-1-129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Specific Antiserum on the Resistance of Neisseria gonorrhoeae to Intracellular Killing by Phagocytes of Human Blood

Abstract: The high natural resistance of gonococci showing a characteristic ' double highlight' (DH) colonial morphology (Penn, Veale & Smith, 19773) to intracellular killing by human phagocytes was markedly reduced by addition of rabbit antiserum to the phagocytosis medium or by preincubation of organisms with antiserum. Antisera raised to three different DH gonococcal strains showed a complex pattern of specificity in phagocytosis tests with the homologous organisms and three other DH strains. The effect of antiserum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…1): in two-dimensional immunoelectrophoresis with antisera against BS4 (agar) the Antiserum against whole organisms. Rabbit antisera to BSDH and BS4 (agar) were raised by multiple intravenous injections of live organisms in Trypticase Soy Broth (TSB; Baltimore Biological Laboratories) as described by Veale et al (1978) for production of hyperimmune antisera. Antiserum to BSDH was used first in the phagocytosis tests but was superseded later by antiserum to BS4 (agar) without any change in the pattern of results.…”
Section: E T H O D Smentioning
confidence: 99%
“…1): in two-dimensional immunoelectrophoresis with antisera against BS4 (agar) the Antiserum against whole organisms. Rabbit antisera to BSDH and BS4 (agar) were raised by multiple intravenous injections of live organisms in Trypticase Soy Broth (TSB; Baltimore Biological Laboratories) as described by Veale et al (1978) for production of hyperimmune antisera. Antiserum to BSDH was used first in the phagocytosis tests but was superseded later by antiserum to BS4 (agar) without any change in the pattern of results.…”
Section: E T H O D Smentioning
confidence: 99%
“…However, the testscan indicatewhether or not intracellular survival and growth occur (Veale et al, , 1978 Counts of extracellular and intracellular gonococci in urethral exudate. Samples from 33 male patients with acute gonococcal urethritis were examined.…”
Section: E T H O D Smentioning
confidence: 99%
“…Rabbit antiserum to BS4 (agar) was raised as described by Veale et al (1978) and Parsons etal. (1981).…”
Section: Estimation Of 2-keto-3-deoxyoctonate and Protein In Omv/ Wgamentioning
confidence: 99%
“…OMV neutralized the ability of antisera raised against whole gonococci to drastically reduce the capacity of strain BS4 (agar) to survive within PMN phagocytes. Furthermore, analysis by SDS-PAGE of OMV/WGA precipitates from lithium chloride extracts of strain BS4 (agar) and strain BSSH, which was more susceptible to phagocyte killing than strain BS4 (agar) and yielded OMV with poor antiserum-neutralizing activity, suggested that three proteins were associated with resistance to phagocyte killing.The capacity of Neisseria gonorrhoeae strain BS4 (agar) to survive within human polymorphonuclear (PMN) phagocytes was drastically reduced by prior treatment with antiserum to whole gonococci (Veale et al, 1978;Parsons et al, 1981), but not if the antiserum was absorbed with surface washes of strain BS4 (agar) (Parsons et al, 1981). This implied that the washes contained a component that determined resistance to killing by PMN phagocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation